Estandarización del proceso de producción de balanceado para perros edad adulta en la empresa Exibal - Bonilla Lata, Robinson Alexander (2023)
The production plant of the “Balanceados Exibal” company dedicated to the production of balanced pet food is located in the Chambo canton. The objective of this research work is to standardize the production process in the elaboration of croquette-type feed for adult dogs, it contains the information on the identification of the activities that are carried out in the elaboration of the feed, in order to Control the production process and determine the status of the production process through the use of control charts. In the present investigation, samples analyzed to determine the capacity to comply with the production specifications and the stability of the process, obtaining a class A process, that is, capable and stable with a Cp= 1.60, a Cpk=1.34 and a St=0%. Time measurements made in each process to determine the standard time through the application of the Westinghouse qualification method, which includes the additional times established by the International Labor Organization, thus obtaining a standard time of 165.18 min (2h: 45 min: 11 sec) in the preparation of 1 ton of feed for adult dogs. A manual prepared for the production of kibble-type balanced food for adult dogs in presentation of 30 kg polyethylene bags, with procedures, instructions and records, which intended to serve as a guide for production personnel who require it.